Analysis of the Effect of Work Environment and Work Motivation on Employee Performance with Work Discipline As an Intervening Variable in PT Hutama Binjai Infrastructure Works - Brandan Zone2 - Mirwan Arif Irfani; M. Isa Indrawan; Kiki Farida Ferine (Yayasan Multidimensi Kreatif, 2023)
This study is intended to test and analyze the direct and indirect impact of the influence of the work environment and work motivation on employee performance with work discipline as an intervening variable at PT Hutama Karya Infrastruktur Binjai - Brandan Zone 2. The research approach uses quantitative research methods. The sample in this study amounted to 80 respondents. Data collection techniques in this study are interviews, literature studies, and questionnaires. The analysis technique used is SEM (Structural Equation Modelling) which is operated through the Smart PLS 4 program. The results of direct effect research show that the work environment has a positive and significant effect on employee performance, motivation has a positive and significant effect on employee performance, work discipline has a positive and significant effect on employee performance, the work environment has a positive and significant effect on work discipline, and motivation has a positive and significant effect on work discipline. While the results of the indirect effect test show that the work environment has a positive and significant effect on employee performance through work discipline at PT Hutama Karya Infrastruktur Binjai - Brandan Zone 2. And work motivation has a positive and significant effect on employee performance through work discipline at PT Hutama Karya Infrastruktur Binjai - Brandan Zone 2.